CONRADT GÖTKE – ENGRAVER OF THE FIRST HALF OF&NBSP;THE 17TH CENTURY - LIŠKEVIČIENĖ, JOLITA (Knygotyra, 2010)
The article presents the engraver Conradt Götke – the most famous artist-graver who worked in Vilnius in the first half of the 17th century. The study aimed to replenish the list of his works – illustrated books. The list of the new bibliographical data is published in the appendix of the article. On the ground of these data, the peculiarities and significance of C. Götke’s works in the history of Lithuanian art of the 17th century are discussed. According to the signed engravings and on the basis of formal similarity of the samples it was established that the artist worked in Vilnius in 1636–1653. C. Götke enriched books and Lithuanian book art with the following features: 1) illustrations of a high artistic quality gave an extra visual information on the text: C. Götke used to add to the text particular artworks with an explicite meaning of the text subject; 2) C. Götke was the first to popularise the copper engraving technique in Vilnius prints; he was the first to amplify several composition patterns typical of his hand; the precise line-drawing and accurate line-engraving allowed him to create an individual artistic language; 3) C. Götke popularised the Baroque style language in Vilnius book illustrations; he used to engage largely popular hieroglyphic, emblematic as well as heraldic symbols in combination with inscriptions; 4) C. Götke intensely collaborated with various clients – high and middle rank nobles of the Grand Duchy of Lithuania, clerks in holy orders, members of the royal family; 5) Götke’s illustrations developed the subject of genealogical and heraldic relations of particular noble families of the Grand Duchy of Lithuania. Some of his art-works are valuable and authentic portrayals of important 17th century personalities; such images are often supplied with inscriptions indicating names and official positions. Götke’s oeuvre is an exceptional phenomenon in the field of book illustration of the 17th century in the Grand Duchy of Lithuania and Poland. Götke’s works prompted the development of book illustration and the formation of a peculiar artistic language of Baroque; the artist sought for a greater variety of motifs and subjects of his compositions. C. Götke is a good example of the social position of an artist in the 17th century: he was a freelance artist-townsman who actively portrayed customers, had a wide circle of clients and created invaluable documents of the 17th century nobility life.